Targeting DNA Damage Repair for Immune Checkpoint Inhibition: Mechanisms and Potential Clinical Applications - Sun, Wei; Zhang, Qing; Wang, Runkun; Li, Yang; Sun, Yue; Yang, Lin (Frontiers in Oncology, 2021)
DNA damage repair (DDR) pathways play an essential role in maintaining genomic integrity. DDR dysfunction leads to accumulated DNA damage, predisposition to cancer, and high sensitivity to chemotherapy and radiotherapy. Recent studies have demonstrated that DDR status is associated with response to immune checkpoint inhibitors (ICIs). Among the DDR pathways, mismatch repair is one of the most recognized predictive biomarkers for ICIs. Furthermore, preclinical and early clinical studies suggest the rationale of combining agents targeting the DDR pathways, such as poly (ADP-ribose) polymerase (PARP) inhibitors, cyclin-dependent kinase 4/6 (CDK4/6) inhibitors, and ataxia telangiectasia and rad3-related (ATR) kinase inhibitors, with ICIs. In the present review, we describe the predictive role of DDR pathways in ICIs and summarize the advances in potential combination strategies of novel agents targeting DDR with ICIs for cancer treatment.